2011
DOI: 10.2166/wp.2011.047
|View full text |Cite
|
Sign up to set email alerts
|

The economic value of water in metropolitan areas of the United States

Abstract: Water has been a passionately contested issue in the United States (US) over the past century. Some argue for growth restrictions in drought-susceptible regions, but based on economic production, it may be worthwhile implementing creative measures to ensure continued and sustainable growth. The following economic analysis correlates water withdrawals in the 32 most populous metropolitan areas in the US with several economic indicators, including gross metropolitan product (GMP), income, and employment. The rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Rather than focus on what type of water conservation policy is better than another, our approach begins with a broad descriptive and explanatory question about the range of water conservation policies: what are the conditions-social, political, economic, hydrological, and technological-that facilitate or impede transitions to an integrated water management regime with highly developed conservation measures? Previous studies have begun to address this question at the state-government level [e.g., Rashid et al, 2010] and at the city-government level [e.g., Gerrity and Snyder, 2011;Teodoro, 2010]. We build on this approach by providing both quantitative and qualitative analyses that draw on both hydrological and social science perpsectives.…”
Section: 1002/2015wr016943mentioning
confidence: 99%
“…Rather than focus on what type of water conservation policy is better than another, our approach begins with a broad descriptive and explanatory question about the range of water conservation policies: what are the conditions-social, political, economic, hydrological, and technological-that facilitate or impede transitions to an integrated water management regime with highly developed conservation measures? Previous studies have begun to address this question at the state-government level [e.g., Rashid et al, 2010] and at the city-government level [e.g., Gerrity and Snyder, 2011;Teodoro, 2010]. We build on this approach by providing both quantitative and qualitative analyses that draw on both hydrological and social science perpsectives.…”
Section: 1002/2015wr016943mentioning
confidence: 99%
“…The model demonstrated that temporary resources should be sufficient to extend the southern Nevada water supply out to at least 2059, even during a shortage condition, but the demand associated with the growing population would eventually deplete the water bank unless additional water policies were implemented. According to Gerrity and Snyder (), the Las Vegas metropolitan area generates approximately $460,000 in gross metropolitan product (in 2015 U.S. dollars) for every million gallons of water withdrawals. The shortages in Table would amount to a minimum net present loss of $650 million for the baseline RFC scenario and $21 billion for the shortage scenario.…”
Section: Resultsmentioning
confidence: 99%
“…In 2011, three papers examined sectorial water allocations and re-allocation (Juana, Strzepek et al 2011;Lennox and Diukanova 2011;Movik 2011). Gerrity and Snyder (2011) examined the economic value of urban water usage in the US, Tarawneh (2011) examined management of a national water supply to cope with drought, Keramitsoglou and Tsagarakis (2011) look at the effectiveness of water saving educational campaigns, while Radulovich (2011) examined potential freshwater savings by increasing human food production in the oceans. These papers relating to adaptation to water scarcity had collectively received six citations by the end of 2011, suggesting that papers on this theme are of above average interest compared to other thematic focuses of water policy.…”
Section: Adaptation To Water Scarcitymentioning
confidence: 99%